Implementasi Program Pengembangan Sumberdaya Manusia dan Pemberdayaan Masyarakat Kelautan dan Perikanan di Desa Teluk Bakau Kecamatan Gunung Kijang Kabupaten Bintan - Siti Utari, Diah; suhardi mukhlis; ayu dwi astuti; Dwiniati, Dwiniati (STISIPOL Raja Haji, 2022)
Human Resource Development Program and empowerment of marine and fishery communities in Teluk Bakau Village, Gunung Kijang District, Bintan Regency. Is a program contained in the Strategic Plan of the Marine and Fisheries Service of the Riau Islands Province which is a form of transfer from the Bintan Regency Fisheries Service as it should, but in implementation The program still has some obstacles in its implementation. The form of this program is managed by the Department of Maritime Affairs and Fisheries of the Riau Islands Province to help fishermen in the mangrove bay area to develop their potential in terms of fisheries and marine affairs.The purpose of this research is basically to find out how to implement the Human Resource Development Program and empower the marine and fisheries community in Teluk Bakau Village, Gunung Kijang District, Bintan Regency. In this study, the respondents consisted of five DKP staff of the Riau Islands Province and one fisherman group and one village staff. The data analysis technique used in this research is descriptive qualitative method with purposive sampling technique. The results of this study conclude that the Human Resource Development program and the empowerment of marine and fishery communities in Teluk Bakau Village, Gunung Kijang District, Bintan Regency have been implemented but are still not optimal, there are several things that must be improved in the program. The advice given so that this program can run optimally is to improve the guidance and coordination of the implementation of marine and fisheries development to the local community. Field fisheries assistants are still very minimal in Teluk Bakau Village, not comparable to the existing active fishing groups.